Produção, aplicação e análise de um curso conectivista para a aprendizagem de astronomia observacional - Moraes, Leandro Donizete (2021)
Even though Astronomy is important for human development, its teaching is still in its infancy in many schools in Brazil. Likewise, the teaching of Astronomy in non-formal spaces has several problems, such as the small number of these spaces and their poor distribution in the country. The lack of basic knowledge about observational astronomy also contributes to the problems faced by this science. The internet can be an ally for learning Astronomy, as it connects many people through resources that can help in learning. In this thesis we analyze one of the possibilities for internet learning, which are the massive open online courses – MOOCs. These courses can provide quality content and diverse resources for learners to study at flexible times and locations. The xMOOCs are courses with a standardized format, which have video lessons and texts, for example, and the cMOOCs are produced in the light of Connectivism and prioritize interactions between participants. Faced with the problems faced by Astronomy, especially by observational astronomy, such as the lack of observation of the sky, for example, this thesis investigates the contributions of a connectivist course for learning observational astronomy. Questionnaires and analyzes of interactions between participants were used for data collection. Data analysis was carried out in the light of documental analysis of the course, discursive textual analysis of questionnaires, quali-quantitative analysis of access logs and analysis of social networks. Among the results, the interactions between the participants contributed to the learning of astronomical concepts and phenomena, the resources used were adequate for this learning and a learning community was built, with an emphasis on social networking.